Pengukuran Kinerja PT Tristanista Global Indonesia Melalui Balanced Scorecard Performance dan Swot Analysis - Nararya Ngurah Lukas Wijaya (CV.ITTC INDONESIA, 2024)
PT Tristanista Global Indonesia is a company engaged in the distribution and marketing of medical and laboratory equipment. Currently, it is known that PT Tristanista Global Indonesia has been using only financial metrics to measure its performance. This focus on financial aspects alone has become a significant issue, as it is insufficient to guide the company through today's and future competitive business landscapes. Therefore, this research aims to evaluate the company’s performance using the Balanced Scorecard and subsequently formulate strategies using SWOT Analysis to enhance the company's performance by leveraging its opportunities. The research results indicate that the overall performance measurement of PT Tristanista Global Indonesia, using the Balanced Scorecard method for the years 2021-2023, yielded a total score of -0.33. This score categorizes the company's performance as poor based on the rating scale. Following this, a strategic formulation was conducted using the SWOT Analysis on the SWOT diagram. It was determined that PT Tristanista Global Indonesia is positioned in Quadrant III, which supports the W-O (Weaknesses-Opportunities) strategy, commonly known as a turnaround strategy. In this context, as indicated by the SWOT Quadrant results, PT Tristanista Global Indonesia is advised to exploit available opportunities to address its internal weaknesses.